Bowel dysfunction after anterior resection for rectal cancer. (1st November 2022) - Burch, Jennie; Taylor, Claire; Wilson, Ana; Norton, Christine
Abstract : Following bowel surgery for rectal cancer, which involves removal of part of the rectum in a procedure termed an anterior resection, bowel problems are often reported by patients. Collectively, symptoms are referred to as low anterior resection syndrome (LARS). A recently published definition of this phenomenon describes a range of bowel symptoms and the consequences and impacts they have on a person's lifestyle and quality of life. It is useful to understand what changes occur after an anterior resection and why, to be able to give appropriate information to patients preparing for an anterior resection about what to expect after surgery and to assist with symptom management after surgery.